Post-fire evolution of ravel transport regimes in the Diablo Range, CA - H. L. Jacobson; D. L. Roth; G. Walton; M. Zimmer; M. Zimmer; K. Johnson; K. Johnson (Earth Surface Dynamics)
Post-fire changes to the transport regime of dry ravel, which describes the gravity-driven transport of individual particles downslope, are poorly constrained but critical to understand as ravel may contribute to elevated sediment fluxes and associated debris flow activity observed post-fire in the western United States. In this study, we evaluated post-fire variability in dry ravel travel distance exceedance probabilities and disentrainment rates in the Diablo Range of central coastal California following the Santa Clara Unit Lightning Complex fire of August 2020. Between March 2021 and March 2022, we conducted repeat field experiments simulating ravel with in situ particles (3–35 mm diameter) on a range of experimental surface gradients (0.38–0.81) on both grassy south-facing slopes and oak woodland north-facing slopes. We characterized post-fire evolution in particle transport by fitting a probabilistic Lomax distribution model to the empirical travel distance exceedance probabilities for each experimental particle size, surface gradient, and time period. The resulting Lomax shape and scale parameters were used to identify the transport regime for each subset of simulated ravel, ranging from “bounded” (light-tailed or local) to “runaway” (heavy-tailed or nonlocal) motion. Our experimental results indicated that as vegetation recovered over the first 2 years post-fire, the behavior of small particles (median intermediate axis of 6 mm) became less similar across the experimental sites due to different vegetation structures, whereas medium and large particles (median intermediate axes of 13 and 28 mm, respectively) exhibited a general transition from more runaway to more bounded transport, and large particles became less sensitive to surface gradient. All particle sizes exhibited a decrease in the length scale of transport with time. Of all particle subsets, larger particles on steeper slopes were more likely to experience nonlocal transport, consistent with previous observations and theory. These findings are further corroborated by hillslope and channel deposits, which suggest that large particles were preferentially evacuated from the hillslope to the channel during or immediately after the fire. Our results indicate that nonlocal transport of in situ particles likely occurs in the experimental study catchment, and the presence of wildfire increases the likelihood of nonlocal transport, particularly on steeper slopes.